On Module Temperature in Floating PV Systems - Peters, Ian Marius; Nobre, Andre M. (Conference Record of the IEEE Photovoltaic Specialists Conference, 2020)
Conventional wisdom has it that floating PV systems have a performance advantage due to a, typically not further specified, cooling effect of water. But how much does the presence of water really contribute to the cooling of PV panels? In this case study, we explore the temperatures of two PV systems located next to one another at a site in Cambodia. One of these systems is mounted on a roof, and one is floating on a pond nearby. For these two installations, we show simulated and measured temperature data. Our analysis suggests that the presence of water does not have a direct effect of the temperature of the floating installation. Differences in the performance of the two sites are best explained by different cooling due to wind. We additionally observe differences in thermal inertia. Overall, we find that, at least without further measures, water bodies only have an indirect effect on PV panel temperature via other factors such as ambient temperature or wind.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Floating PV; Modelling and Simulation